HYSTERICAL FEMININITY IN NICK JOAQUIN'S THE WOMAN WHO HAD TWO NAVELS - Lao, Christine Veloso (Sanata Dharma University, 2024)
This essay presents a reading of Nick Joaquins The Woman Who Had Two Navels through the lens of feminist scholarship on the history and social construction of female hysteria. It argues that a critical intertextual reading of this sort affirms the heteropatriarchal foundations of popular ideations of the Philippine nation. It uses Sara Mills Feminist Stylistics to draw attention to Joaquins discourse on women, specifically, hysterical women such as Connie Escobar. It argues that the discourse of the novelits reliance on the stereotype of the hysterical feminine woman, its focalization through a male gaze, and its employment of the schemata of women asking for itexplains why readers find Connie Escobars inconsistent behavior and characterization not only plausible but even subversive. However, reading the novel from the lens of feminist stylistics also reveals instances where the novel reinscribes patriarchal ideology. Any reading that views Connie as a metaphor for the Philippine nation must therefore confront the patriarchal ideology that informs this vision of the nation.